Raising Backyard Chickens for Eggs - Mary E. Henry; Jessica M. Ryals; Alicia Halbritter; Derek L. Barber (EDIS)
Raising backyard chickens is an increasingly popular way to explore self-sufficiency, connect with how our food is produced, and gain experience for future dabbling in food production. This 13-page publication is designed primarily for those considering raising backyard chickens for eggs for personal consumption. Written by Mary E. Henry, Jessica M. Ryals, Alicia Halbritter, and Derek L. Barber, and published by the UF/IFAS Department of Animal Sciences, revised November 2019. https://edis.ifas.ufl.edu/an239